Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Step-by-step explanation:
To prove that: (2cosA+1) (2cosA-1) = 2cos2A+1
We try to solve one side of the equation to get the other side of the equation.
In this case, we'll solve the right hand side (2cos2A + 1) of the equation with the aim of getting the left hand side of the equation (2cosA + 1)(2cosA - 1)
Solving the right hand side: 2cos2A + 1
i. We know that cos2A = cos(A+A) = cosAcosA - sinAsinA
Therefore;
cos2A = cos²A - sin²A
ii. We also know that: cos²A + sin²A = 1
Therefore;
sin²A = 1 - cos²A
iii. Now re-write the right hand side by substituting the value of cos2A as follows;
2cos2A + 1 = 2(cos²A - sin²A) + 1
iv. Expand the result in (iii)
2cos2A + 1 = 2cos²A - 2sin²A + 1
v. Now substitute the value of sin²A in (ii) into the result in (iv)
2cos2A + 1 = 2cos²A - 2(1 - cos²A) + 1
vi. Solve the result in (v)
2cos2A + 1 = 2cos²A - 2 + 2cos²A + 1
2cos2A + 1 = 4cos²A - 2 + 1
2cos2A + 1 = 4cos²A - 1
2cos2A + 1 = (2cosA)² - 1²
vii. Remember that the difference of the square of two numbers is the product of the sum and difference of the two numbers. i.e
a² - b² = (a+b)(a-b)
This means that if we put a = 2cosA and b = 1, the result from (vi) can be re-written as;
2cos2A + 1 = (2cosA)² - 1²
2cos2A + 1 = (2cosA + 1)(2cosA - 1)
Since, we have been able to arrive at the left hand side of the given equation, then we can conclude that;
(2cosA + 1)(2cosA - 1) = 2cos2A + 1
Answer:
[tex]\boxed{\sf LHS = RHS }[/tex]
Step-by-step explanation:
We need to prove that ,
[tex]\sf\implies (2 cosA +1)(2cosA-1) = 2cos2A+1[/tex]
We can start by taking RHS and will try to obtain the LHS . The RHS is ,
[tex]\sf\implies RHS= 2cos2A + 1 [/tex]
We know that , cos2A = 2cos²A - 1 ,
[tex]\sf\implies RHS= 2(2cos^2-1)-1 [/tex]
Simplify the bracket ,
[tex]\sf\implies RHS= 4cos^2A - 2 +1 [/tex]
Add the constants ,
[tex]\sf\implies RHS= 4cos^2-1 [/tex]
Write each term in form of square of a number ,
[tex]\sf\implies RHS= (2cos^2A)^2-1^2 [/tex]
Using (a+b)(a-b) = a² - b² , we have ,
[tex]\sf\implies RHS= (2cosA+1)(2cosA-1) [/tex]
This equals to LHS , therefore ,
[tex]\sf\implies \boxed{\pink{\textsf{\textbf{ RHS= LHS }}}} [/tex]
Hence Proved !
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.